EVALUASI PROSES PENGELOLAAN OBAT DENGAN PRIORITAS ANALISIS PADA PEMBOROSAN (WASTE) DALAM PROSES PENGADAAN OBAT DI INSTALASI FARMASI RUMAH SAKIT SANTA MARIA PEMALANG - , Tjia Lilian Trisnawati Prasetya, Dr. Erna Kristin, M.SI,Apt ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: With the implementation of the Badan Penyelenggara Jaminan Sosial (BPJS) on January 1, 2014 with payment systems Indonesian Case-Based Group (INA-CBGs), the hospital is required to act as efficiently as possible while still maintaining the quality. The approach which appropriate with this condition is lean management that identify waste that disrupt the flow of the process and prioritize the value from the patient's perspective. Considerable components in financing and relatively easy to intervention are medication. So the process of medication management in pharmacy must be done as efficiently as possible. Repair problems are prioritized on a selected medication management processes. Objective: To identify the root cause of the problem of waste in the medication management process priority in Santa Maria Hospital pharmacy, Pemalang using lean management approach. Methods: Using a case study research design type of explanatory, making data comes from several sources, namely the study of documents, observation and focus group discussions with the entire pharmacy staff and other staff associated with the management of medication in the pharmacy. The study explores the root causes of waste in the process of medication management priorities so the research is a case study of single stranded (embedded). Results and discussion: Problems in the medication management process quite much, but the priority for medication management process improvement is procurement process. Waste in the process of drug procurement, among others: overprocessing, overproduction, human potential, waiting, inventory, motion, transportation, that cause process cycle efficiency only 7.68%. The root cause of waste such as: poor communication between the warehouse staff and procurement staff, drug procurement budget planning not available, ordering drugs do not pay attention to the minimum inventory and ordering medication administration time, poor communication with suppliers, organizing functions of pharmacy and therapeutics committee yet run, structuring the work area is not adequate. Conclusion and recommendation The problem occurs on the drug management process quite a lot, and the most prominent is the procurement process due to waste.